2020
DOI: 10.1088/1757-899x/753/4/042036
|View full text |Cite
|
Sign up to set email alerts
|

Heritage Protection Regulations in Germany and their Relations to Fire Safety Demands

Abstract: Historical constructions are an important value of the world’s cultural heritage. Nearly each day, newspapers inform about fire damages in protected buildings. One reason is that historical constructions often are very fire sensible due to ancient building methods and easily flammable building materials. Therefore, fire safety regulations contribute in an essential way to the countries’ heritage protection. Furthermore, they avoid personal injury, property loss and environmental damage. Heritage protection law… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…They generally are devoid at the same level of fire safety systems as modern buildings. More difficulty is encountered in attempts to install fire safety JFM 21,4 systems in old buildings than in modern buildings (Quapp and Holschemacher, 2020;Akashah et al, 2016). Therefore, this paper is also aimed to investigate the fire safety compliance in the government hospital buildings, as there are many government hospitals established before the law enforcement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They generally are devoid at the same level of fire safety systems as modern buildings. More difficulty is encountered in attempts to install fire safety JFM 21,4 systems in old buildings than in modern buildings (Quapp and Holschemacher, 2020;Akashah et al, 2016). Therefore, this paper is also aimed to investigate the fire safety compliance in the government hospital buildings, as there are many government hospitals established before the law enforcement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Old or historic buildings are, in general, more vulnerable to fire (Torero, 2019;Raneri, 2021), which is why the most recent studies highlight the importance of investigating the vulnerability of each building, considering the context in which they are inserted and their unique needs, to understand how their structure influences the overall fire performance (Torero, 2019;Bakas et al, 2020;Salazar et al, 2021;Romão & Bertolin, 2022;Petrini et al, 2022 ). The bibliographic review identified some of the characteristics that make historic buildings vulnerable to fire, namely: the presence of numerous wooden structures; the absence of adequate compartmentalization; the impossibility of altering the original characteristics of the building; uncertainty regarding techniques and materials used in the original construction; the existence of voids and other elements with low fire resistance; insufficient number of alternative exits; long distances to travel, in the sense of evacuation; storage of flammable substances; non-compliance of electrical installations; difficulties in accessing emergency services and the absence of active fire detection and suppression systems (Naziris et al, 2016;Iringová & Idunk, 2017;Torero, 2019;Devi & Sharma, 2019;Kincaid, 2020;Quapp & Holschemacher, 2020;Caliendo et al, 2020;Castillo et al, 2021;Cao et al, 2021;Huang, 2022;Petrini et al, 2022). The old or historic buildings were built at a time when the principles of fire safety were not observed, presenting, for this reason, characteristics that make it challenging to apply a set of prescriptive requirements present in the current regulations.…”
Section: Main Considerations Of the Literature Review On Fire Safety ...mentioning
confidence: 99%
“…In general, the assessment of these buildings carried out based on prescriptions, leads to the identification of non-conformities, for which it is necessary to find equivalent and exceptional solutions, which can entail high costs (Torero, 2019;Bakas et al, 2020;Vijay et al, 2021;Kincaid, 2022;Petrini et al, 2022;Romão & Bertolin, 2022). The concern with the design of fire safety in heritage buildings and protected structures has stimulated research to develop new methodologies, improve existing ones, and assist decision-making in the application of a more holistic view (Naziris et al, 2016;Kincaid, 2018Kincaid, , 2019Bakas et al, 2020;Caliendo et al, 2020;Romão & Bertolin, 2022), which combines principles of fire safety engineering and conservative principles, which safeguard the heritage value (Kincaid, 2018;Torero, 2019;Pau, 2019;Bakas et al, 2020;Quapp & Holschemacher, 2020). The research of potential innovative solutions requires more significant investment.…”
Section: Main Considerations Of the Literature Review On Fire Safety ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Venegas et al [31] examined significant fires in historic buildings between the years 1990 and 2019, highlighting some noteworthy aspects of them. Quapp and Holschemacher [32] analysed the current German regulations regarding preservation and reconstruction of heritage structures and stressed the complexity to find the right balance between protection and safety, giving useful additional information about fire protection approaches in such kind of structures.…”
Section: Literature Reviewmentioning
confidence: 99%